Perception and Healthcare Seeking Behavior in Acute Respiratory Infection among Parents of Under Five Children attending a Tertiary Care Center of Banke - Chand, Ambika; Ranjitkar, Uma Devi (Journal of Institute of Medicine Nepal, 2024)
Introduction Acute Respiratory Infections (ARI) are one of the leading and common causes of morbidity and mortality in children worldwide affecting under five children. Compared to high income countries, the incidence and frequency of ARIs pose a significant burden in low- and middle-income countries. The purpose of the study was to find out the perception and health care seeking behavior of ARI among parents of under five children. Methods A cross-sectional descriptive design with non-probability purposive sampling was used in the Pediatrics outpatient department of Nepalgunj Medical College Teaching Hospital. Data were collected using interview semi-structured questionnaires. A total of 187 parents attending OPD with their children were included in the study. Ethical approval was obtained from Nepal Health Research Council. Descriptive and inferential statistics used to analyze finding. Results Sixty-five percent respondents were from age 25–35 years. Among them two-third were female; 44.4%. educated, 42.8% were homemaker. Nearly half of the respondents had single child; 40.6% of children between 1-3 years; two- third (67.4%) were male. Majority (97.3%) had heard about acute respiratory infections and aware about acute respiratory infections. Majority (94.1%) perceived pneumonia as one of the common respiratory infections and (89.8%) perceived about cold exposure as cause of ARI. Conclusion More than half parents perceived about ARI in under five children. Almost all aware about increase temperature and respiratory distress were severe symptoms of ARI and there were significant association with knowledge and socio demographic variables such as ethnicity, education and occupation.